Equations in One Variable VI Equations OneVariable Variable VI Equations in One Variable VI Equations ininOne VI o of a function f(x) is a number z E R such that f(z) = 0. zero a function fof (x) a number ∈ R such that = 0.that f(z) = 0. A zero is such z Ef (z) f(x) a number R= such zero AA of of a function isa aisfunction number z Ez R f(x) that f(z) 0. ples. Examples. Examples. Examples. The number 1 is a zero of the function loge(x). That’s because • The number is a zero That’s becauseThat’s because •1 The number 1function isfunction a zerologe(x). oflog the function loge(x). e (x). loge(1) = 0. • The number 1 is a zero of of thethe That’s because loge (1) = 0. loge(1) = 0. loge(1) = 0. JOSe () JOSe () JOSe () 6 is a zero of the function x 6. That’s because [6] 6 = 0. a zero − 6. That’s because [6] 6−=6because = 0. [6] isfunction •the 6function a zerox ofx the function x 6. [6]That’s • 6• is6 is a zero of of the 6. That’s because 0. — — — — / // 4 / // 4 — — 6 = 0. // 4 / To state a more general version of the previous example, a is a zero • To state a more of previous aexample, zero • general Togeneral stateversion aversion moreofgeneral versionexample, ofexample, the previous a is a zer of x a. • To state a more thethe previous a isa aiszero of x a. of of x x− a. a. — — — x-a 278 / 278 312 / 278 x-a / x-a 2 Thefunction functionx x . .• The 2x The function 2 − 9has has zeros 3and and −3. 9 9has zeros 3 3and zeros —3. —3. —— Thezeros zerosofof ofa apolynomial apolynomial polynomial are called roots. • ••The are called roots. The zeros are called roots. x ehas hasnono nozeros. zeros. • •• e’e’ has zeros. xx Theset setofof ofzeros zerosofofof sin(x) {. . .—27r, ,—27r, −2π, −π, 0,r,π, 2π, 3π, . . .}. • ••The sin(x) isisis —7r, 2r, The set zeros sin(x) —7r, 2r, 0,0,r, 3ir,. 3ir,. {... {... .. That is, the set of zeros of sin(x) is the set That Thatis,is,the theset setofofzeros zerosofofsin(x) sin(x)isisthe theset set { nπTi|Tin ∈ Z} {n7r Z} {n7r Z} , Sin() Sin() 313 279 279 , Finding zeros of functions zeros functions Finding ofof zeros Finding of functions zeros functions Finding Iff(x) f (x) isfunction, function, then the zeros off(x) f (x) are the solutions ofthe the equation equation then thethe zeros of of f(x) are thethe solutions of of the If If f(x) isIfis af(x) then the zeros ofare f(x) are the solutions of the equation is a function, equation then zeros solutions aafunction, f (x) f(x)=O. = 0. f(x)=O. f(x)=O. Examples. Examples. Examples. Examples. The zeros ofthe the linear polynomial 2x+5 +are are the solutions ofthe the of of the zeros the linear 2x2x+ solutions . The of zeros of thepolynomial linear polynomial are the solutions . zeros The oflinear polynomial solutions .•The of 52x5are +the5the the 5 . Thus, equation 2x + 5 = 0. Subtract 5: 2x = −5. Then divide by 2: x = − 2: 2:x = equation 2x2x 5: 5:2x2x = 5: —5.—5. bydivide equation 2xThen =Then —5.divide Then = 5 Subtract 0. Subtract + 5+ 5 2x0. +0.Subtract equation = divide by xby=2: xThus, 2 Thus, Thus, 5 isthe the only zero of2x 2x+ 5. + 5. −is2isthe only zero of of 2x 5. isonly the only zero of+5.2x + zero —. —. — — —. — 2.5 2.52.5 2 2 2 The zeros oflog(x logofe (x 2)are are the solutions oflog(x logofe (x 0.This ThisThis of of 2)−2)=2)=0.=0.2)This • The zeros log(x 2)−2)are the solutions log(x • zeros Theof zeros log(x 2)the aresolutions the solutions log(x = 0. ••The of 0 equation isequivalent equivalent −= 1,and and thus isequivalent equivalent to toxtox x 3. equation is isequivalent to toxtoxx2to 1,=1,and is isequivalent to=3.x3. 3. equation is equivalent 2e = = = thus 1,thus and thus is equivalent equation 2 2x== = That is the only zero ofthe the function loge (x −2).2). 2). function loge(x 2). That is, is, 3is,is33is the zero of of the loge(x That is,the 3only isonly the only zero offunction the function loge(x That zero — — — — — — — — — — — — 1o (x-2) 1o (x-2) 1o(x-2) z(t3z(t3 z(t3 2 2 The zeros ofx x 4x+3 −4x+3 are the solutions ofthe the equation x 4x+3 −4x+3 zeros of of thethe solutions of of the equation 0.=0.0. = 0. • The —x 2 x 4x+3 — 2 x 4x+3 zeros of x are the solutions of the equation •zeros The —=4x+3 2 x —are 2 4x+3 are solutions equation = ••The — 2 — 2 Using the quadratic formula, we can find that the solutions are 1are and 3. 3. that thethe solutions areare 1 1and Using the quadratic formula, wewe can find 3.1 3.and that the solutions Using the quadratic formula, we can find that solutions and Using the quadratic formula, can find 2 Therefore, and are zeros ofx −4x 4x+ 3. + 3. thethe zeros of of 2 x Therefore, 1 and 3 1are 3.+3.4x arezeros the zeros of 2 x + Therefore, 3the are 2x 4x Therefore, 11and 33and — — — II I 33 314 280280 280 3 √ √ • The zeros of the2+ function x − 3 are of solutions . The zeros of the function are solutions = 0. x − 3 = 0. /‘x √23 + 2+ \/x of 32 + This equation is equivalent x − and 3 = thus −2, and has no solutions This equation is equivalent to /x 3to= —2, it hasthus solutions √no it 3 has no zeros. since square-roots never negative. since square-roots are never are negative. Therefore,Therefore, 2 + /x 23 + has xno−zeros. — — — — 3 An illustration when not to divide An illustration of whenofnot to divide asked find the solutions of the equation If asked toIf find thetosolutions of the equation (x − 1)(x − 2) = 3(x − 1) (x—1)(x—2)=3(x—1) be to tempted to divide sides of the by equation (x − 1) leaving you mightyou be might tempted divide both sidesboth of the equation (x 1) by leaving with 2) = 3,simpler a muchequation. simpler equation. while (xis− 2) = 3 is However, However, while (x —2) you with you (x —2) = (x 3, − a much = 3 a muchequation simpler (the equation (thetosolution is 5)equivalent it is not equivalent certainly certainly a much simpler solution it is 5) to it isit not to theequation original (x—1)(x—2) equation (x−1)(x−2) = That’s 3(x−1). That’sthe because the function to the original = 3(x—1). because function (x a−zero 1) has 1), and multiplying dividing an by equation by (x 1) has (thea zero zero (the is 1), zero and ismultiplying or dividingoran equation function zero in theofdomain of the isequation is not a valid way has athat zerohas in athe domain the equation not a valid way a functiona that of obtaining an equivalent of obtaining an equivalent equation. equation. steps below the describe theprocess generalforprocess solving equations of the below solvingforequations of the The stepsThe describe general form h(x)f (x) = h(x)g(x). After thesteps, general we’ll return to the form h(x)f(x) = k(x)g(x). After listing thelisting general we’llsteps, return to the example of (x − 1)(x − 2)1). = 3(x − 1). example of (x 1)(x —2) = 3(x — — — — Steps for solving (x) = h(x)g(x) solving Steps for h(x)f(x)h(x)f h(x)g(x) = Stepthe 1: Find theofdomain of the equation. CallD.this set D. Step 1: Find domain the equation. Call this set Stepthe 2: Find zerosthat of h(x) D. set CallZ.this Z. The numbers Step 2: Find zeros the of h(x) are inthat D. are Callinthis Thesetnumbers will be solutions of h(x)f (x) = because h(x)g(x)ifbecause in Z will in be Zsolutions of h(x)f(x) = h(x)g(x) h(z) = 0if h(z) = 0 then = h(z)f (z)==00f = 0==h(z)g(z). 0g(z) = h(z)g(z). then h(z)f(z) Of(z) = (z) Og(z) Stepthe 3: Find the solutions of the h(x)f(x) equation = h(x)f (x) = with h(x)g(x) Step 3: Find solutions of the equation h(x)g(x) the with the D −function Z. The h(x) function h(x) hasinnoDzeros restrictedrestricted domain Ddomain Z. The has no zeros Z, in D − Z, you can with by dividing h(x) to the equivalent theobtain equivalent so you cansostart withstart dividing h(x) tobyobtain f (x) = g(x). equation equation f(x) = g(x). — — Step 4:the Collect and the solutions Step 3. These Step 4: Collect zeros the fromzeros Stepfrom 2 andStep the 2solutions from Stepfrom 3. These are the solutions of theequation. original equation. are the solutions of the original 281 315 Examples. • Let’s return to the equation (x−1)(x−2) = 3(x−1) and proceed through the four steps outlined above. . Let’s of the 2 16)equation, (x 1og(x) =so(2 16). (Step 1): find (x −the 1)(xsolutions − 2) = 3(x − 1)equation is a polynomial the domain is R.(Step Written in the notation of the general D= 1): The domain of the equation is steps because weR.can only take (0, oc),above, the logarithm a positive (Step 2): The of function thatnumber. we’d like to divide both sides of the equation by — — is (x(Step − 1).2): Its The zero is 1, which solution of (x − 1)(x − 2) = zeros of (x 2will be 16) aare the solutions of 2 16 3(x = − 0, 1)or since ([1] − 1)([1] 2) = 0(−1) 0 = 3(0)are = 43([1] 1). However, Written of inthese the equivalently, the − solutions of x 2 == 16, which and−—4. = (2 notation of the above, = {1}.of (x two zeros, onlygeneral 4 is insteps the Z domain (0, oc), 2 16) 16) log(x), so it’s the zero to of find 2 the (x 16) solutions that concerns in this problem. (Step 3): only We need of theusequation (x − 1)(xWith − 2) the = notation of the general steps listed Z above, = {4}. 3(x − 1) with the restricted domain of R − {1}. On this domain, the function (x −(Step 1) has so find we can by of (x(x − 1).16)The resulting 3): no Wezeros, need to the divide solutions 2 loge(x) 16) with = (x 2equivalent equation is (x −domain 2) = 3.(0,We add The 2 to function see that (x the solution is xzeros = 5.in the the restricted oo)can{4}. 2 16) has no set (0, 4): oc) The {4}. we cannumber divide the equation 2 16)ofloge(x) = (x (Step zeroTherefore, of (x − 1)—the 1—and the solution 2 16)−by2) (x 2 the equivalent equation loge(x)5—are = 1. The (x(x − 1)(x = 3(x16)− to 1) obtain with domain R − {1}—the number the only solution of 1)(x this − equation is − x = 1To = e. solutions of (x − 2) = 3(x 1).e repeat, the set of solutions of the equation 1)(xsolutions − 2) = 3(x 5}. = (x 4):−The (Step (x of − 21) is4){1, (x loge(x) 2 4) are 2 (from Step 2) and e (from Step 3). — — — — — — — — — — — — — — — (x -;)Cx-z 5 316 283 Examples. • Let’s find the solutions of the equation (x2 − 16) loge (x) = (x2 − 16). —2) because = 3(x —1) and proceed through • Let’s to the equation (x is1)(x (Step 1): Thereturn domain of the equation (0, ∞), we can only take the four steps outlined above. the logarithm of a positive number. — polynomialof equation, domain 1): (x 3(x are1) the is a solutions (Step (Step 2): The zeros1)(x of —2) (x2 −= 16) x2 − 16 so = the 0, or of which the general steps−4. above, D = JR. is R. Written in the notation equivalently, the solutions of x2 = 16, are 4 and However, of these 2 2 both thelog equation by (Step 2):4 The we’d likeofto(x divide two zeros, only is infunction (0, ∞), that the domain − 16) = sides (x −of16) e (x), 2 of (x 1)(x With 2) = the 3(x 1) (x only 1).zero Its zero which be a solution so it’s isthe of (xis −1, 16) thatwill concerns us in this problem. ([1] general 2) listed = O(—1) 1). Written in the since 1)([1] steps = 0 notation of the above, Z == 3(0) {4}. = 3([1] thetogeneral steps above,ofZ(x=2 − {1}. (Stepnotation 3): We of need find the solutions 16) log (x) = (x2 − 16) with — — — — — — — — — e 3): We (0, equation (Step domain need to find the the restricted ∞)−{4}. Thesolutions function of (x2the −16) has no (x zeros 1)(x in the 2) = 2 domain, withTherefore, the restricted domain of the JR equation {1}. On this set (0,3(x ∞) −1){4}. we can divide (x − 16) logthe = e (x)function 2 2 divide by (x 1). The (x by 1) (x has−no16) zeros, so we the can equivalent (x − 16) to obtain equation logeresulting (x) = 1. equivalent The 1 equationofisthis 2) = 3. isWex = cane add (x equation only solution = e.2 to see that the solution is x = 5. — — — — — — — 2 1and solution of 2) (Step 4):solutions The zeroofof(x(x 1)—the number (Step 4): The − 16) loge (x) = (x2 − 16) arethe4 (from Step 1) with domain JR {1}—the number 5—are the (x 1)(x 2) = 3(x and e (from Step 3). solutions of (x 1)(x 2) = 3(x 1). To repeat, the set of solutions of the equation (x 1)(x —2) = 3(x 1) is {1, 5}. — — — — — — — — — — (a 282 317 x • Let’s •find thefind solutions of xex = . Let’s the solutions of exeX = e’. (Step 1): The1):implied domaindomain is R. is R. (Step The implied eX has (Step 2): ex has zeros. (Step 2): no no zeros. x = e cx (Step 3): Dividing xex = xex ex by yields equivalent equation x = 1.x (Step 3): Dividing yields the equivalent equation by eX the Thus, 1Thus, is the1 only is thesolution. only solution. = 1. (Step 4): There no are zeros so 1 2,is SO the1 only 4): are (Step There nofrom zerosStep from2,Step is thesolution. only solution. i x 2 • Let’s •find thefind solutions of (x +of2)e(x2x+=2)e (x +=2)e Let’s the solutions (xx .+ 2)ex. (Step 1): The1):implied domaindomain is R. is R. (Step The implied (Step 2): The2):zero of zero (x +of2)(xis +−2. It’s—2. in the of the equation, so (Step The 2) is It’s domain in the domain of the equation, so it’s a solution. it’s a solution. (Step 3): Dividing (x + 2)e(x2x+=2)e (x + 2)e(xx + by2)ex (x +by2) (x gives the us equivalent (Step 3): Dividing ’ 2 the equivalent +2)usgives 2x e 2x x x x 2 = cx. cx to = 1 which the same equation e = ee . We canWe then e tobyget equation candivide then by divide = 1 is which is the same ex get 2x−x x equation as e as=e 1 or = more e = 1.cxApplying the logarithm yields yields equation 2 1 orsimply, more simply, = 1. Applying the logarithm that x = logxe (1) = 0. = 0. that = log(1) x 2 (x +=2)e (Step 4): −2 4): and—2 0 are solutions of (x +of2)e (Step andthe the solutions (x2x+=2)e (xx .+ 2)ex. 0 are 1’ 318 284 * * * * * * * * * * * Chapter Summary The solutions of h(x)f (x) = h(x)g(x) are the solutions of f (x) = g(x) together with the solutions of h(x) = 0. 319 * * Exercises For #1-6, find the zeros, if there are any, of the given functions. 1.) x − 2 2.) 3x + 4 3.) x2 − 81 4.) x2 + 7 √ 5.) 2 x − 7 6.) e3x−2 Find the solutions of the following equations in one variable. √ 7.) x3 x = 9x3 8.) (x − 2)(x3 − 2x)2 = −5(x − 2) 9.) (x − 4)2 loge (x + 2) = 2(x − 4)2 10.) loge (x − 1)ex = −2 loge (x − 1) 11.) −8(x2 − 25) = (x2 − 25)[loge (x)2 − 6 loge (x)] 12.) (2x + 1)5 = 9(2x + 1)3 √ 13.) (x2 − 4) x = −(x2 − 4) 14.) ex x1 + x = 2ex √ √ 15.) e3x x = ex−2 x 16.) (x + 3) loge (2x) = (x + 3) loge (x + 1) 17.) (x − 4)5 = (x − 4)6 18.) (x − 2)(x − 3) = (x − 2)(x + 1) 19.) x = x2 320